(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
• One of the problems not only more recurrent but also more important to the world of art of the 20th century, both the philosophical and the artists, was the departure of beauty as the only legitimizing account of an object which is intended to the status of art. In this sense, the reflection that Arthur Coleman Danto, philosopher of American art (in its origins –although not only in them– analytic philosopher), it has made a career as one of the theoretical positions to confront the art after the beauty and, in addition, to support the need for a definition of the same despite the entropy of the 20th century, which meant the advent of art as a human production already determined not only for beauty but for the ugliness, the repugnance, the industry and a long etcetera.